2021
DOI: 10.3390/educsci11080419
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Faculty Perspectives during Emergency Remote Teaching in Engineering at a Large Public University

Abstract: In Spring 2020, the College of Engineering at San José State University (SJSU) conducted a comprehensive analysis of the impact of COVID-19 on faculty who were forced to transition to an online learning environment. The purpose of this study is to assess the impact of COVID-19 on faculty teaching methods, assessment methods, and personal well-being. The study was a combination of a quantitative survey and a qualitative study using interviews of engineering faculty teaching in Spring 2020. In the first part, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
2
15
0
4
Order By: Relevance
“…This process contains three stages: (1) identifying desired results, (2) determining assessment evidence, and (3) planning instruction to enable students to succeed on the assessments. While faculty were concerned with the possibility that students would cheat on assessments in a virtual setting [23], student comments indicated that the focus on measures to prevent and detect cheating were ineffective, made assessments more difficult, and caused additional stress and anxiety. Many students indicated a desire for real-world contexts to be included in the lessons and topics, consistent with the findings of Means and Neisler [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process contains three stages: (1) identifying desired results, (2) determining assessment evidence, and (3) planning instruction to enable students to succeed on the assessments. While faculty were concerned with the possibility that students would cheat on assessments in a virtual setting [23], student comments indicated that the focus on measures to prevent and detect cheating were ineffective, made assessments more difficult, and caused additional stress and anxiety. Many students indicated a desire for real-world contexts to be included in the lessons and topics, consistent with the findings of Means and Neisler [8].…”
Section: Discussionmentioning
confidence: 99%
“…One way to foster community is to create well-structured student groups that work on assignments both in class and out of class. During the pandemic, when all instruction was taking place at a distance, this was even more critical [2,5,8,19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The lockdown has caused teachers to be more attentive to the factors that cause variations in the teaching-learning results due to the adequacy of the resources available to the students, the suitability of the active learning methodologies used in each subject and the technological differences between academic fields [ 37 , 38 , 39 ]. In addition, there is the fact that much of the academic staff required levels of technological competence higher than those they had previously acquired and that some degrees were more difficult to adapt to online education [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The size of the population was 1384, i.e., the number of full-time students at the faculty in 2020. The margin of error coefficient was assumed at the level of 8%, analogous to the values adopted by the authors in other publications relating to the results of survey research [38,39]. Depending on the study, the confidence level usually amounts between 90% and 99%.…”
Section: Project Description and Preliminary Resultsmentioning
confidence: 99%